Application of the endurance time method to the seismic analysis and evaluation of highway bridges considering pounding effects. (15th January 2017) - Guo, Anxin; Shen, Yu; Bai, Jiulin; Li, Hui
Highlights: The endurance time method is employed for pounding analysis of highway bridges under seismic excitations. The effectiveness and accuracy of the ET method are validated through the comparison of incremental dynamic analysis. The pounding responses can be easily and accurately predicted through a few ET accelerograms. A method is proposed to transfer the ET curves to spectral form for being easily implemented by the engineers. Abstract: Seismic-induced pounding between adjacent segments is a complex contact phenomenon in which the dynamic responses of structures, including pounding effects, are strongly related to structural properties and earthquake excitations. This paper explores the effectiveness and accuracy of the endurance time method for predicting the pounding responses of highway bridges with a reduced simulation effort. A three-span highway bridge was selected as the target structure, and the incremental dynamic analysis results were employed as a basis of comparison for the structure under 22 earthquake records. Based on the observations of the validation, the pounding effects analyses were carried out using the ET method. Finally, the analysis results were transferred into a common spectral form to estimate the pounding force and the other pounding responses. The investigation results indicate that the ET method is sufficiently accurate to be implemented for the seismic analysis and evaluation of highway bridges, with the inclusion of pounding effects.